A Self-Emulsifying Nanococktail of Pomegranate and Cannabidiol Reduces Cognitive Decline in Mice - Shoseyov O; Palatnik A; Dadon-Freiberg M; Dagan O; Shaltiel Karyo R (Nutrition and Dietary Supplements)
Oded Shoseyov,1,2 Avi Palatnik,1 Maayan Dadon-Freiberg,1 Orit Dagan,1 Ronit Shaltiel Karyo1 1Tahiro Inc, Encino, CA, 91436, USA; 2The Robert H. Smith Institute of Plant Science and Genetics, The Faculty of Agriculture, Food and Environment, The Hebrew University of Jerusalem, Rehovot, IsraelCorrespondence: Ronit Shaltiel Karyo, Tahiro Inc, 16130 Ventura Blvd., Suite 570, Encino, CA, 91436, USA, Email ronitsh80@gmail.comIntroduction: Stress and inflammation in the early stages of cognitive decline has spurred interest in the use of antioxidants as prophylactic and therapeutic agents. Several studies have established the neuroprotective capacities of a pomegranate oil nano-formulation (Nano-PSO). In parallel, cannabis-derived cannabidiol (CBD) prevented social recognition deficits and reduced neuroinflammation in mice. This work assessed the impact of Nano-PSO:CBD on memory and learning.Methods: A battery of hemp extracts was screened for their effects on acetylcholine esterase inhibition and neuronal protection activities. The best-performing extract in the in-vitro assays was nano-formulated via self-emulsifying system with PSO and administered to aged mice and mice with MK-801-induced cognitive decline, which were then subjected to a Morris water maze test and Y-maze test, respectively.Results: Aged mice chronically fed Nano-PSO:CBD performed with a 22– 31% shorter escape latency (p ≤ 0.05), 23% shorter distance swam and increased average speed as compared to aged control mice. Mice pretreated with Nano-PSO:CBD prior to MK-801 had a significantly higher percentage of entries into the novel arm of the Y-maze compared to untreated controls.Discussion: PSO nano-formulated with CBD had a salutary effect on memory, learning and spatial recognition and should be further studied in a clinical context.Keywords: cognition, nanoformulation, CBD, pomegranate seed oil, nano-omega 5, brain protect, punicic acid